2019
DOI: 10.4102/sajhrm.v17i0.1161
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with retention factors in relation to job embeddedness of public school teachers

Abstract: Orientation: The major challenge that organisations face in the contemporary competitive environment is to retain talented and productive employees. To ensure that the education system functions optimally, there is a need for strategic human resource management (HRM) practices to be implemented to assist in retaining qualified and experienced teachers.Research purpose: The purposes of this study were to establish the relationship between retention factors and job embeddedness, and to establish whether retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…Thus, this research proffers a contribution through illustrating additional components of public service delivery. This contribution advances work that is already on the ground within the South African public service (Ijeoma et al, 2013;Shibiti, 2019;Zondo, 2018). Whilst this work shows support to previous similar international research (Cummins, 2000;Guo et al, 2017), it becomes the first to proffer these findings from a South African public service context.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, this research proffers a contribution through illustrating additional components of public service delivery. This contribution advances work that is already on the ground within the South African public service (Ijeoma et al, 2013;Shibiti, 2019;Zondo, 2018). Whilst this work shows support to previous similar international research (Cummins, 2000;Guo et al, 2017), it becomes the first to proffer these findings from a South African public service context.…”
Section: Discussionsupporting
confidence: 80%
“…Examples include: (1) unfavourable teacher-learner ratios, (2) student-teacher bullying, (3) fellow teacher absenteeism, (4) constantly increasing administrative burdens, (5) diminished autonomy and finally (6) under-resourced classroom facilities (Ballet, Kelchtermans, & Loughran, 2006;Pyhältö, Pietarinen, & Salmela-Aro, 2011;Skaalvik & Skaalvik, 2010;West & Meier, 2020). These challenges ultimately impact service delivery outcomes (Mafini & Dlodlo, 2014) potentially affecting the teachers and their contribution to service delivery (Shibiti, 2019;Redelinghuys & Rothmann, 2020;Zondo, 2018).…”
Section: The Teaching Profession In South Africamentioning
confidence: 99%
“…These include: (a) maladministration; (b) corruption and (c) the careless use of public resources (Eastern Cape Province Office of The Premier, ). These challenges are noted to be creating strain not just in the quest for service delivery (Fihla & Chinyamurindi, ) but also affecting employees who work in such government departments (Shibiti, ). Despite the Eastern Cape Province is the citadel of the automotive sector, unemployment remains high due to a decline in labour productivity and slow business growth within this sector (Zondo, ).…”
Section: Background Of the Studymentioning
confidence: 99%
“…(Eastern Cape Province Office of The Premier, ), these government units were given attention. Despite research showing the high turnover rate within the South Africa public service (e.g., Shibiti, ; Zondo, ), no link is made as to where these employees who leave the public service end up.…”
Section: Background Of the Studymentioning
confidence: 99%
“…In addition, Allen, Peltokorpin & Rubenstein (2016) proposed that job embeddedness would moderate the relationship between organisational conditions and voluntary turnover outcomes. Shibiti (2019) suggested that there is a relationship between satisfaction with reward, compensation, work environment and other retention factors in relation to job embeddedness. Further, there is a growing need to study job embeddedness as a moderator as little is known about it (Burton et al, 2010;Swider et al, 2011).…”
Section: Moderating Variablementioning
confidence: 99%